Mycotoxins in food : detection and control - Magan, N. (Naresh); Olsen, M. (Monica) (Woodhead Publishing in food science and technology., 2004)
Mycotoxins are toxic compounds produced by fungi. They are produced in foods of plant origin and pose a significant contamination risk in cereal and other foods. With its distinguished editors and international team of contributors, Mycotoxins in food summarises the wealth of recent research on how to assess the risks from mycotoxins, detect particular mycotoxins and control them at differing stages in the supply chain.